2019
DOI: 10.1088/1757-899x/659/1/012087
|View full text |Cite
|
Sign up to set email alerts
|

Testing methods and equipment for palletized products

Abstract: The ability to present cutting-edge solutions for packaging in the field of palletized products has to be considered as the result of the investments in research infrastructures and advances in applied researches. In the present article, main equipment and all the other testing facilities used to optimize palletized product are detailed. Tests are implemented in accordance with standard and no standard procedures up to fully innovative methods. This approach is able to provide advice both on the most appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Juwet et al 14 investigated the horizontal dynamic effects on a palletized unit with short‐duration (0.3 s) and low‐acceleration events (0.5 and 0.8 g) to evaluate the response of unit loads. In another study, Greco et al 15 used an acceleration sled during the simulation of horizontal testing. Dunno and Ge 13 conducted a field measurement to characterize the horizontal events using a straight delivery box truck.…”
Section: Introductionmentioning
confidence: 99%
“…Juwet et al 14 investigated the horizontal dynamic effects on a palletized unit with short‐duration (0.3 s) and low‐acceleration events (0.5 and 0.8 g) to evaluate the response of unit loads. In another study, Greco et al 15 used an acceleration sled during the simulation of horizontal testing. Dunno and Ge 13 conducted a field measurement to characterize the horizontal events using a straight delivery box truck.…”
Section: Introductionmentioning
confidence: 99%
“…The results reported that as the gap increased between the unit load and the vehicle wall, the greater the damage potential 17 . Greco et al 18 utilized an acceleration sled incorporating the same duration and acceleration levels as Juwet et al 17 and was able to compare stretch wrapping patterns and configurations. The Federal Motor Carrier Safety Administration (FMCSA) 19 reports performance requirements for cargo securement systems ranging from 0.05 to 0.8 g depending on the direction of travel and cargo capacity but does not specify the duration of these events and provide no guidance for testing or evaluating this criterion.…”
Section: Introductionmentioning
confidence: 99%
“…Two additional bands of paper with the same circumference are produced to repeat the test. An increasing horizontal inertia forces test: Bundles are almost always stacked in several layers on a pallet for transport by road and possibly rail. During this transport, inertia forces occur in the direction of travel due to acceleration and deceleration of the vehicle and in the transverse direction due to changes in direction 33–41 . In practice, the accelerations and decelerations almost always remain under 2 m/s 2 and occur with intervals of several minutes.…”
Section: Methodsmentioning
confidence: 99%